2020
DOI: 10.1108/vjikms-11-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of knowledge mapping implementation in Indonesian organizational context

Abstract: Purpose Knowledge growth is currently experiencing a very exponential increase, through a digital transformation of knowledge in the organization and the emergence of various platforms through management system content such as blogs and social media that have encouraged such growth. An employee no longer only interacts in knowledge management (KM) in his organization but can communicate and collaborate to share knowledge through these platforms widely. Much of the spread of knowledge is a challenge for organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, knowledge storage can be understood as the company’s “memory”, containing data, information and explicit knowledge (Wang et al , 2007). Also, knowledge mapping should be understood as a critical KM tool in which its research has been carried out in various fields; to make the best use of it, the organization must provide a platform to share knowledge or rather, this “memory”, obtained by the organization (Al Hakim et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, knowledge storage can be understood as the company’s “memory”, containing data, information and explicit knowledge (Wang et al , 2007). Also, knowledge mapping should be understood as a critical KM tool in which its research has been carried out in various fields; to make the best use of it, the organization must provide a platform to share knowledge or rather, this “memory”, obtained by the organization (Al Hakim et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These knowledge maps can also make use of artificial intelligence (AI) with imaging, clinical symptoms, exposure history and laboratory data, creating an algorithm with which to rapidly diagnose COVID-19 in patients. Al Hakim et al (2020) also concluded that the support of technology through the use of AI can be expected to enable comprehensive, adaptive and objective knowledge mapping for organisations.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Al Hakim et al (2020) also concluded that the support of technology through the use of AI can be expected to enable comprehensive, adaptive and objective knowledge mapping for organisations.…”
Section: Training Education and Communicationmentioning
confidence: 99%
See 1 more Smart Citation